2019
DOI: 10.3390/e21121219
|View full text |Cite
|
Sign up to set email alerts
|

Finite Amplitude Stability of Internal Steady Flows of the Giesekus Viscoelastic Rate-Type Fluid

Abstract: We investigate the finite amplitude stability of internal steady flows of viscoelastic fluids described by the Giesekus model. The flow stability is investigated using a Lyapunov functional that is constructed on the basis of thermodynamical arguments. Using the functional, we derive bounds on the Reynolds and Weissenberg number that guarantee the unconditional asymptotic stability of the corresponding flow. Further, the functional allows one to explicitly analyse the role of elasticity in the onset of instabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 130 publications
(164 reference statements)
0
7
0
Order By: Relevance
“…The reader interested in more involved applications of the proposed construction is kindly referred to Appendix A , where we discuss the stability the spatially inhomogeneous steady temperature field in a rigid body wherein the heat conductivity is a function of the temperature. Application to the flows of polymeric fluids is discussed in Dostalík et al [ 50 ], where the authors analyse the stability of the Taylor–Couette type flow of the Giesekus fluid. Finally, Dostalík and Průša [ 51 ] use the proposed method in a coupled thermal convection/conduction setting.…”
Section: Discussionmentioning
confidence: 99%
“…The reader interested in more involved applications of the proposed construction is kindly referred to Appendix A , where we discuss the stability the spatially inhomogeneous steady temperature field in a rigid body wherein the heat conductivity is a function of the temperature. Application to the flows of polymeric fluids is discussed in Dostalík et al [ 50 ], where the authors analyse the stability of the Taylor–Couette type flow of the Giesekus fluid. Finally, Dostalík and Průša [ 51 ] use the proposed method in a coupled thermal convection/conduction setting.…”
Section: Discussionmentioning
confidence: 99%
“…However, we recall that we have not discussed the relation between the functional and a metric structure on the state space; hence, the functional does not, at the moment, deserve to be referred to as the Lyapunov functional. See also Dostalík et al [50,51] for a similar application in the case of macroscopic viscoelastic rate-type models, where the authors have actually found a relation between the proposed Lyapunov type functionals and a metric on the state space. Inspecting (119) and (118), we also note that the time derivative of V meq is proportional to the net entropy production that vanishes at the stationary spatially homogeneous equilibrium state (81).…”
Section: Solvent Part: Noble-abel Stiffened-gas Equation Of Statementioning
confidence: 91%
“…(The metric is constructed using the Bures-Wasserstein distance on the set of positive definite matrices, see Bhatia et al [15].) For details regarding this concept we refer the interested reader to Dostalík et al [16].…”
Section: Decay Of Perturbations -Mechanical Quantitiesmentioning
confidence: 99%